Parental Attachment, Peer Influence and Adolescent Sexual Behavior at Vocational High School Trenggalek Regency - Shafira Meidy safitri; Zakiyatul Faizah; Euvanggelia Dwilda Ferdinandus (Jurnal KESANS : Kesehatan dan Sains, 2022)
Introduction: Adolescence is a transitional phase from childhood to adulthood characterized by a heightened curiosity and courage to take risks. SDKI data from 2012 and 2017 showed an increase in cases of adolescents who had had premarital sexual intercourse, with the breakdown of cases in adolescent boys by 4.5% then increasing to 8% and in adolescent girls by 0.7% increasing to 2%. Objective: this study is to determine the relationship between parental attachment and peer influence with adolescent sexual behavior. Method: The type of research is correlational analytics with a cross-sectional approach. The study was conducted at SMKN 1 Pogalan, Trenggalek Regency in June 2022. The population used was grade 11 students of SMKN 1 Pogalan with a sample of 86 people. Sampling using simple random sampling. Data analysis used the spearman rho test with a 95% confidence level. Results and Discussion: Based on correlational tests, results were obtained that the variables of maternal attachment (p=0.002), father's attachment (p=0.001), and peer influence (p=0.000) had a value of p<0.05. Conclusion: this study shows there is a relationship between parental attachment and peer influence with adolescent sexual behavior in Trenggalek District Vocational High School